THE IMPACT OF INTERNSHIP PROGRAMS ON PROSPECTIVE TEACHERS' READINESS TO TEACH - Wardah Anggraini; Budi Hartono (Indonesian Journal of Education and Youth Development, 2025)
This study aims to determine the impact of the School-Based Internship Program (PLSP) on students' readiness to conduct teaching practice. The research employs a quantitative approach through a survey method involving students from the Economic Education Study Program who have participated in the internship. The findings indicate that the internship program significantly influences students’ readiness in planning, implementing, and evaluating learning. Students felt more confident and better understood real teaching contexts after completing the program. These findings highlight that PLSP is a crucial component in preparing competent and professional future educators.